Fruits in Melaka Heritage Garden - Mohamed, Noorizan; Ani, Anisa; Abd Rahman, Nordin; M. Razali, Meor Mohamad Fared (University Putra Malaysia, 2012)
The study summarized that fruit trees found in the planting composition of traditional Malay gardens in Melaka are filled with meaning and symbolism while meeting the household needs through a variety of functions over the years. Bright-coloured fruit trees in the front yard represent the “house pride element” of the resident, also as landmarks for the residence itself. Plant allocation in the compound area, may consist of the meaning or symbolism of an important event from the past. Coconut palm (C. nucifera) has been used to symbolise the birth of a family member. Pinang palm (Areca catechu) is famous as an indication of the first day of house construction. The large trunk feature in trees, such as the Durian (Durio zibethinus), significantly help to demarcate land.